Weight stigma and mental health in a racially and ethnically diverse sample of US adults - Mary A. Gerend; Anna W. Lu; Elizabeth L. Teets (Frontiers in Psychiatry, 2025)
IntroductionWeight stigma is associated with poor mental health outcomes. Yet little is known about whether the strength of the association between weight stigma and mental health outcomes differs by race or ethnicity, or factors that mitigate the mental health consequences of weight stigma. This study sought to address these research gaps.MethodsA large sample of US adults (N = 2,632; aged 18–64 years; 50% women) completed an online survey. Quota sampling ensured that over two-thirds of respondents self-identified as Black/African American or Hispanic/Latino. Our primary predictors were experienced and internalized weight stigma. Primary outcomes included global mental health, depression severity, and history of diagnosis with a depressive disorder. Linear and logistic multivariable regression analyses tested whether the association between weight stigma and mental health outcomes was moderated by (1) race or ethnicity, and (2) frequency of using adaptive coping strategies to manage weight stigma-related stress (e.g., cognitive reframing, seeking social support).ResultsBoth experienced and internalized weight stigma were associated with worse mental health (i.e., lower global mental health scores, more frequent depressive symptoms in the past two weeks, greater odds of depressive disorder diagnosis) and effects held while controlling for body mass index and sociodemographic characteristics. Further, the strength of the association between weight stigma and mental health outcomes was equivalent among Black and non-Black participants and among Latino and non-Latino participants. Adaptive coping was a significant moderator for global mental health and depressive disorder diagnosis but not depression severity such that the weight stigma-mental health relationship was weakest among respondents who engaged in adaptive coping strategies more frequently.DiscussionAdults with more frequent exposure to interpersonal weight stigma and higher levels of internalized weight bias reported poorer mental health status. Notably, the strength of these associations was similar regardless of racial or ethnic identity suggesting no group is protected from the detrimental health effects associated with weight stigma. Individuals who respond to weight stigma with adaptive coping strategies may be more protected from adverse psychological outcomes. Findings have important implications for initiatives aimed at reducing harm to mental health that may be associated with weight stigma.